Frequency of Pterygium Recurrence with Limbal Stem Cell Autograft - Irfan Qayyum Malik, Muhammad Sharjeel, Farhan Ali (Pakistan Journal of Ophthalmology, 2016)
Purpose: To determine the frequency of recurrence of pterygium with limbal stem cells autograft. Study Design: Descriptive, case series study. Place and Duration of study: Department of Ophthalmology, Mayo Hospital Lahore for eight months (1st January 2013 till 31st August). Material and Method: There were 120 cases aged between 30-60 years of both genders. Included patients had primary Pterygium encroaching cornea up to 2 mm from limbus. Patients with Pseudopterygium, recurrent Pterygium and active ocular infection were excluded. All the selected patients underwent limbal stem cell autograft technique for pterygium treatment and recurrence was noted after 6 months post-operatively. Results: Mean age was 41.18 ± 11.03 years with majority of the patients i.e. 38 (31.67%) were between 41 to 50 years of age. Out of these 120 patients, 79 (65.83%) were male and 41 (34.67%) were females with ratio of 1.9:1. Pterygium recurrence was found in only 06 (5.0%) patients. Therefore the success rate was 95.0%. Conclusion: Limbal stem cells autograft with pterygium excision significantly reduces the recurrence of Pterygium surgery. Keywords: Pterygium, surgical treatment, autografts, recurrence.